Show-ha shoten! Volume 6 - Asakura, Akinari, 1989- (Shonen Jump manga., 2024)
"Shy Azemichi Shijima has secretly been studying the art of comedy. His outgoing classmate Taiyo Higashikata has big dreams of being funny but no follow-through. When the two team up, they just might take the comedy world by storm! Defeated by Rising at the High School Comedy Battle and faced with their lack of experience compared to Broken Glass Slipper at the Hiyama Cup, Azemichi and Taiyo must grapple with yet another loss. But now it's time to travel to Osaka, where the ten best comedy duos in the nation have gathered! This is the start of the competition that will crown the best high school comedians in the country, the Wara-1 Koshien!!"--Back cover.